Analysis of the Influence of Religious Beliefs and Solidarity on Product Boycott Behavior - Nabila Salwa Amarta; Ihwan Susila (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the impact of religious belief and social solidarity on the boycott behavior of pro-Israel products. A quantitative descriptive approach was used with random sampling to select 101 participants who met the criteria, using a closed-ended questionnaire consisting of 30 statements focused on intrinsic and extrinsic factors influencing boycott behavior. The primary data were collected directly from the respondents. The variables in this study include two independent variables, religious belief (X1) and social solidarity (X2), and one dependent variable, boycott behavior (Y). The population of this study consisted of residents in Surakarta who were involved in the boycott movement. The analysis of data included tests for validity and reliability, classical assumptions (normality, multicollinearity, and heteroscedasticity), and both simple and multiple linear regression analysis. Hypothesis testing was conducted using t-tests, F-tests, and the coefficient of determination (R²). The results reveal that both religious belief and social solidarity significantly positively influence boycott behavior. The higher the level of religious belief and social solidarity, the greater the tendency to engage in the boycott as a form of support for Palestine. Simultaneously, these two variables explain 74.2% of the variation in boycott behavior, highlighting the importance of religious belief and social solidarity in motivating individuals to participate in social movements. The study also suggests that other factors, such as brand loyalty or media influence, which were not analyzed in this study, may affect boycott behavior and should be considered in future research.